Scientific Learning Training by School Principals to Improve Teacher Competence - Wildan; Yusuf (Letiges, 2024)
High school teachers whose educational background is only D-III and who are then appointed civil servants provide challenges for supervisors in developing their competence in various aspects of learning. One action is to improve teachers' skills in implementing scientific learning through training organized by school principals. This research examines how scientific school principals carry out learning training. This type of research is classroom action research. The subjects in this research were teachers at SMA Negeri 1 Janapria. This research uses a three-cycle design with four stages: planning, action, observation and reflection. The research results of three cycles proved that the actions taken successfully increased teacher competence according to the expected standards. The percentage of teacher competency rose from 58.13% in Cycle I to 70.13% in Cycle II, then increased again to 81.88% in Cycle III. Thus, the research results show that the training organized by the school principal effectively increased teacher competency, with a completion rate reaching 100%, and received a positive response from the teachers. Scientific learning training carried out by school principals has succeeded in increasing teacher competence, obtaining positive reactions from them, improving the quality of learning, and has the potential to improve overall school performance.